2017
DOI: 10.4102/sajpsychiatry.v23i0.1083
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying factors associated with the discharge of male State patients from Weskoppies Hospital

Abstract: BackgroundDesignated psychiatric facilities are responsible for the care, treatment and reintegration of State patients. The necessary long-term care places a considerable strain on health-care resources. Resource use should be optimised while managing the risks that patients pose to themselves and the community. Identifying unique factors associated with earlier discharge may decrease the length of stay. Factors associated with protracted inpatient care without discharge could identify patients who require ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
4
5
0
Order By: Relevance
“…In South Africa, variable prevalence rates of SUD amongst psychiatric inpatients have been found. 10,14,29,30,31 Our results are similar to the 62% prevalence of a current SUD found amongst acute psychiatric patients in the Western Cape, 29 and to the 72% prevalence found amongst a sample of Gauteng state patients. 14 Using the ASSIST questionnaire in a study at a regional psychiatric hospital in KwaZulu-Natal, South Africa, 22 patients were reported to have a similar 54% recent alcohol use and 43% recent cannabis use.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In South Africa, variable prevalence rates of SUD amongst psychiatric inpatients have been found. 10,14,29,30,31 Our results are similar to the 62% prevalence of a current SUD found amongst acute psychiatric patients in the Western Cape, 29 and to the 72% prevalence found amongst a sample of Gauteng state patients. 14 Using the ASSIST questionnaire in a study at a regional psychiatric hospital in KwaZulu-Natal, South Africa, 22 patients were reported to have a similar 54% recent alcohol use and 43% recent cannabis use.…”
Section: Discussionsupporting
confidence: 83%
“…9 Having a SUD increases the risk of violent behaviour in community and acute inpatient settings 10,11,12,13 and, in South Africa, it is associated with a longer duration of admission amongst male state patients. 14 Finally, suicidal behaviour, completed suicide and all-cause mortality are all increased in the presence of a comorbid SUD. 15,16,17,18,19,20 Background: Mental disorders and substance use disorders (SUD) commonly occur together, impacting healthcare outcomes.…”
mentioning
confidence: 99%
“…12 The findings are comparable with the emotion-focused coping mechanisms used by caregivers of people with mental illness, namely, tolerance, positive http://www.sajpsychiatry.org Open Access thinking and help seeking, whilst social support helped them to cope with the psychological distress. 7 Similar to research findings in the same study context, 21 families in this study indicated that the absence of high-risk behaviour such as substance abuse and aggression facilitates trust during leave that increases the likelihood of SPs being discharged.…”
Section: Discussionsupporting
confidence: 80%
“… 4 , 7 , 8 The high rate of substance use has been a consistent finding in other South African studies and has been associated with longer admission periods and higher rates of recidivism. 13 , 23 …”
Section: Discussionmentioning
confidence: 99%